Luminescence mechanisms of silicon-rich nitride films fabricated by atmospheric pressure chemical vapor deposition in N(2) and H(2) atmospheres - Lin, Chia-Hung; Uen, Wu-Yih; Lan, Shan-Ming; Huang, Yen-Chin; Liao, Sen-Mao; Li, Zhen-Yu; Yang, Tsun-Neng; Ku, Chien-Te; Chen, Meng-Chu; Huang, Yu-Hsiang (My University, 2009)
This work examines possible luminescence mechanisms of silicon-rich nitride (SRN) films that were fabricated by atmospheric pressure chemical vapor deposition (APCVD). Under an ambient gas of either H(2) or N(2), two SRN films were deposited using the same precursors of Si and N. While photoluminescence (PL) measurements of both as-deposited specimens revealed an intense luminescence band (1.8-3.8 eV), which was observable by the naked eye, a detailed examination of the high energy band of the PL spectra over 2.8 eV yielded different results for those samples that were fabricated in different ambiences. To determine the reason for these differences, Fourier-transform infrared spectroscopy and x-ray photoelectron spectroscopy were conducted, suggesting unique chemical bonds and elemental ratio of nitrogen to silicon in SRN films. Further analysis involving plan-view high-resolution transmission electron microscopic observations of SRN films demonstrated the embedding of Si quantum dots (Si QDs), but with some differences depending on the deposition environment. Analyses of the results obtained suggest that the emission from SRN films that were deposited by APCVD is not only dominated by the quantum confinement effect of Si QDs, but also subordinately affected by the surface states around these Si QDs.